2016
DOI: 10.1016/j.jspd.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Scoliosis and Thoracolumbar Kyphosis in Patients With Achondroplasia

Abstract: Level 3 or 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
1
17
0
2
Order By: Relevance
“…The literature regarding natural history, medical complications and morbidity rates in adults remains rather limited, as also reported by Thompson et al in 2008 . However, some larger studies have more recently been conducted on pain, HRQOL, orthopedics and spine, as shown in Table . In the following, we will discuss some of the key findings of the identified studies, as also presented in Tables and , including study limitations and identified knowledge gaps.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The literature regarding natural history, medical complications and morbidity rates in adults remains rather limited, as also reported by Thompson et al in 2008 . However, some larger studies have more recently been conducted on pain, HRQOL, orthopedics and spine, as shown in Table . In the following, we will discuss some of the key findings of the identified studies, as also presented in Tables and , including study limitations and identified knowledge gaps.…”
Section: Discussionmentioning
confidence: 81%
“…Mild scoliosis, defined as Cobbs angel >10°, was found in 55 of 98 adults, and moderate to severe scoliosis (Cobbs angel >25°) was found in 12/98 adults. Mild thoracolumbar kyphosis, defined as the curvature >10° to 25° at the thoracolumbar junction (T11‐L2), was seen in 26/98 adults, while severe thoracolumbar kyphosis (curvature >25°) was seen in 45/98 adult individuals …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations